The Relationship Between Perceived Ad Morality and Behavioral Intentions Exploring the Mediation Effect : Indian Women’s Perspective Using Structural Equation Modeling - Kazi, Roshan; Singh, Archana; Sharma, Adya (Prabandhan: Indian Journal of Management, 2018)
Purpose : Writings on advertising ethics are huge. This paper analyzed that women are dehumanized, as beauty industries misrepresent their images and their portrayal. The fundamental purpose of this study was to confirm the relationships between ’perceived morality in ads’ and ’behavioral intentions’. Further, it also aimed to confirm mediation effect of ’feelings’ and ’advertiser belief’ between ’perceived morality in ad’ and ’behavioral intentions’. Methodology : This paper considered a female perspective in evaluating morality in Indian ads, which was empirically tested using structural equation modeling. The study was conducted in Pune city of India by employing cross - sectional design. An integrative conceptual model was developed and tested by employing SEM using AMOS 21 (analysis of moment structures). Findings : The results suggested that the relationship between ’perceived morality in ads’ and ’behavioral intentions’ was mediated by ’feelings’ and ’advertiser beliefs’. Further, ’feelings’ and ’advertiser beliefs’ were antecedents to ’behavioral intentions’. No significant relationship was found between ’feelings’ and ’advertiser beliefs’. Originality/Value : This paper contributed to the existing literature by proposing a framework of the interrelationships of ’feelings’ and ’advertiser beliefs’. An integrative conceptual model was developed and tested for the first time to understand the female perspective in evaluating morality in Indian ads.